Predictor for premature coronary artery disease (PCAD) in Asian populations: a meta‑analysis - Baskoro, Shalahuddin Suryo; Adelathifa Rahma, Oktivani; Arthalia, Virra Dennisa Rahmandasari; Maulana, Muhammad Zacky Hafiyyan; Waranugraha, Yoga; Rohman, Mohammad Saifur (Heart Science Journal, 2026)
Background: Premature coronary artery disease (PCAD) is a major cause of heart disease in Asian populations, where coronary events happen at younger ages than in Western populations. Evidence concerning PCAD risk factors is inconsistent, in part due to variability in comparator selection among studies. Objective: To assess clinical and metabolic risk factors linked to PCAD in Asian populations through comparator-specific meta-analysis Method: According to the PRISMA 2020 guidelines, we did a systematic review and meta-analysis. We searched PubMed/MEDLINE, Cochrane, Scopus, and Web of Science for studies published from 2020 onwards. We included studies that looked at risk factors for PCAD in Asian groups with either non-CAD or older/later-onset CAD comparators. We used random-effects models to combine mean differences for continuous variables and odds ratios for categorical variables. We used I² statistics, funnel plots, and Egger's regression test to look at publication bias and heterogeneity. Results: Sixteen studies comprising 187,591 participants, including 28,943 patients with PCAD, were included. In pooled analyses, smoking (OR 2.18, 95% CI 1.74–2.72; p<0.001) and family history of premature cardiovascular disease (OR 2.11, 95% CI 1.74–2.55; p<0.001) were significantly associated with PCAD, while hypertension (OR 0.75, 95% CI 0.63–0.90; p=0.002) showed an inverse association. In the non-CAD comparator subgroup, stronger associations were observed for smoking (OR 2.56, 95% CI 1.83–3.58; p<0.001), hypertension (OR 2.34, 95% CI 1.63–3.35; p<0.001), male sex (OR 1.90, 95% CI 1.34–2.69; p<0.001), and family history (OR 3.99, 95% CI 1.10–14.51; p=0.040). HDL levels were consistently lower (MD −4.34 mg/dL and −9.52 mg/dL in both comparator groups), while triglycerides and non–HDL-C were higher. Elevated fasting blood glucose and C-reactive protein were observed only in non-CAD comparisons. LDL-C showed no significant difference across analyses. Conclusion: Predictors linked to PCAD in Asian populations differ based on the choice of comparators. Traditional cardiovascular risk factors, especially smoking and familial history, exhibit the most significant correlations, underscoring the necessity of early risk detection and prevention in younger populations.